Introduction: The Protection of Law - L. McNamara (Law Text Culture, 2008)
Who needs law’s protection? Who does law protect? Does law need protection from politicised abuses? Can we restore law to a rightful place in the social? Did it ever have one? These were the provocations of the call for papers for the Australasian Law and Society Conference, on the ambiguous and unsettling theme ‘The Protection of Law’. The works featured in this special issue of Law Text Culture have their origins in two events held at the University of Wollongong in 2006 and 2007. The first was that conference, hosted by the University’s Legal Intersections Research Centre and Faculty of Law in December 2006.